PARTISIPASI MASYARAKAT PADA PROSES PEMBENTUKAN PERDA PROVINSI BALI DALAM RANGKA MEWUJUDKAN GOOD GOVERNANCE - Zenith Syahrani; I Gusti Ngurah Wairocana; Cok Istri Anom Pemayun (Kertha Negara : Journal Ilmu Hukum, 2013)
According to Article 1 paragraph (2), The 1945 Contitution of the Republic of Indonesia, fourth amendment, sovereignty is in the hands of the people and is implemented according to this Constitution. That article explicitly explained that people has role in government practice through involve in people participation in the process of making regulation, in this case Peraturan Daerah Provinsi Bali. On the other side, participation has also becomes an important indicator in the effort of achieving a Good Governance. How is the mechanism and the type of that people participation? And what is the relevancy between participation and Good Governance? This paper uses normative legal method and descriptively analyzed, it will explicate the rules of the mechanism of people participation in government practice based on the regulation and its relevancy with the effort of achieving Good Governance.